Paediatric rheumatologists do not score the physician's global assessment of juvenile idiopathic arthritis disease activity in the same way - Backström M; Tarkiainen M; Gottlieb BS; Trincianti C; Qiu TT; Morgan E; Lovell DJ; Bovis F; Löyttyniemi E; Ruperto N; Vähäsalo P; Consolaro A (OXFORD UNIV PRESS, 2025)
Objectives: To assess the heterogeneity in factors affecting physiciańs global assessment of disease activity (PhGA) and in PhGA scoring of multiple juvenile idiopathic arthritis (JIA) patient's case scenarios.
Methods: An electronic web-based questionnaire of factors potentially considered in PhGA was sent worldwide to members of the Paediatric Rheumatology International Trials Organisation (PRINTO) and the Pediatric Rheumatology Care and Outcomes Improvement Network (PR-COIN). The respondents were asked to rate from 0 to 100 the relevance of 17 factors possibly affecting PhGA scoring and to derive a PhGA score of 17 detailed JIA patient cases. The median and interquartile range was used to measure the heterogeneity in the scoring. To demonstrate the consistency among the PhGA scores of the patient cases provided by multiple physicians, we assessed the inter-rater reliability using intra-class correlation (ICC).
Results: The questionnaire was completed by 491 respondents. A large individual variation was observed in the impact of different factors on PhGA when assessing JIA. For non-systemic JIA the presence of fever had the largest variation and swollen joint count had the smallest. For sJIA, the largest variation was seen in the presence of erosions and the smallest in the presence of fever. The ICC of the group for PhGA scoring of patient cases was 0.53 (95%CI: 0.38-0.72).
Conclusions: In a sample of worldwide respondents, the scoring of the PhGA is divergent. Consensus on PhGA scoring guidelines is required to obtain a consistent assessment of patients.